Digital literacy as a form of citizenship education in the era of technological disruption - Siti Maizul Habibah; Lidiawati; Ita Yunita; Nor Ardyanti Ahmad; Nuruddin (C-DISC, 2026)
The era of technological disruption has profoundly transformed various aspects of human life, including civic education. Rapid advances in digital technology require citizens not only to adapt but also to develop strong digital literacy to participate critically and responsibly in the digital public sphere. This study examines the role of digital literacy as a form of civic education in the era of technological disruption and explores its contribution to strengthening responsibility, legal awareness, and media ethics. A qualitative literature review was conducted by analyzing relevant national and international scholarly publications published between 2020 and 2025. The findings indicate that digital literacy extends beyond technical competence, serving as a moral and social foundation that enables citizens to think critically, participate actively, and act ethically in digital environments. Integrating digital literacy into civic education enhances democratic awareness, encourages meaningful civic participation, and reduces the misuse of digital technologies, including the spread of misinformation and hate speech. These findings highlight the strategic importance of digital literacy-based civic education in preparing citizens to respond effectively to the challenges of technological disruption. Strengthening digital literacy within civic education is therefore essential for fostering adaptive, responsible, and ethical citizens capable of contributing to democratic and inclusive digital societies.